Concurrent training promoted sustained anti-atherogenic benefits in the fasting plasma triacylglycerolemia of postmenopausal women at 1-year follow-up - Rossi, Fabrício E.; Diniz, Tiego A.; Fortaleza, Ana C.S.; Neves, Lucas M.; Picolo, Malena R.; Monteiro, Paula A.; Buonani, Camila; Lira, Fábio S. [UNESP]; Freitas, Ismael F. (My University, 2018)
The aim of this study was to compare the effects of aerobic and concurrent training (aerobic plus strength training) on the lipid profiles of normotriacylglycerolemic and hypertriacylglycerolemic postmenopausal women and to verify whether the benefits of aerobic and concurrent training were sustained after 1 year. Total cholesterol, high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol, triacylglycerol (TAG), and glucose were assessed in 46 normotriacylglycerolemic (TAG < 150 mg•dl-1) postmenopausal women divided into 3 groups: aerobic training, concurrent training (CT), and a control group. For CT group, hypertriacylglycerolemic postmenopausal women were recruited (TAG ≥ 150 mg•dl-1, n = 14). Total daily caloric consumption and free-living physical activity were evaluated by dietary questionnaires and accelerometer, respectively, and fat mass by DXA. In 16 weeks, CT was effective in increasing HDL-c (normotriacylglycerolemic: pre = 57.1 ± 17.3 mg•dl-1 X post = 64.3 ± 16.1 mg•dl-1 p = 0.020 and hypertriacylglycerolemic: pre = 44.7 ± 9.6 mg•dl-1 X post = 50.3 ± 15.3 mg•dl-1; p = 0.012) and reducing the atherogenic index in normotriacylglycerolemic (pre = 3.6 ± 0.9 mg•dl-1 X post = 3.0 ± 0.6 mg•dl-1; p = 0.003) and hypertriacylglycerolemic (pre = 5.2 ± 1.1 mg•dl-1 X post = 4.7 ± 1.2 mg•dl-1; p = 0.018) postmenopausal women. In addition, the effects were sustained at the 1-year follow-up only among the hypertriacylglycerolemic postmenopausal women. The anti-atherogenic status in normotriacylglycerolemic and hypertriacylglycerolemic postmenopausal women was changed by CT but without significant differences between groups. Furthermore, these benefits are sustained at the 1-year follow-up among the hypertriacylglycerolemic subjects.